Economic Governance Reforms to Support Inclusive Growth in the Middle East, North Africa, and Central Asia - Jarvis, Christopher (Departmental Papers; Departmental Paper ;, 2021)
This IMF Departmental Paper presents the key areas in which countries of the Middle East, North Africa, and the Caucasus and Central Asia (MECA) can enhance governance and fight corruption to achieve their economic policy goals. It draws on advances that have already taken hold in the region.